The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

La reconnaissance de l’homoparenté au Québec. Lorsque les stratégies de mobilisation de la communauté rencontrent l’avant-gardisme de l’État - Côté, Isabel; Lavoie, Kévin (Revue des politiques sociales et familiales, 2018)
Résumé Cet article retrace les jalons historiques ayant mené à l’institutionnalisation de l’homoparenté au Québec et met en lumière la synergie entre les revendications d’associations gaies et lesbiennes et les interventions étatiques de l’appareil gouvernemental. La décriminalisation de l’homosexualité au Canada en 1969, puis l’ajout de l’orientation sexuelle comme motif illicite de discrimination dans la Charte québécoise des droits et libertés en 1977 ont posé les bases juridiques sur lesquelles s’est ancrée la reconnaissance des couples de même sexe et des familles homoparentales aux tournants du nouveau millénaire. Les stratégies de mobilisation déployées par les groupes militants se sont alors inscrites dans les filières institutionnelles de l’action publique, à la rencontre des interventions progressistes de l’État québécois. L’analyse rétrospective de cette lutte offre une meilleure compréhension de la transformation des représentations familiales contemporaines et des débats actuels en matière de filiation.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; hétéronormativité; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; maternité; parentalité; premier cycle; privilèges; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc2262; soc2264; sociologie; systèmes d'oppressions; thématiques

Rapport sur le racisme vécu par la communauté LGBTQ+ montréalaise - Almeida, Jade (Conseil Québécois LGBT, 2017)
Le 18 août dernier, nous avons soumis au Ministère de l’Immigration, de la Diversité et de l’Inclusion (MIDI) un projet en réponse à l’appel pour réaliser une Consultation sur le racisme systémique afin que la Commission tienne notamment compte de l’intersection entre le racisme et les LGBTphobies dans ses consultations. Notre proposition a été acceptée selon le premier mandat qui avait été choisi par le ministère. En dépit de l’évolution de ce dernier, le Conseil québécois LGBT a souhaité poursuivre la mission qu’il s’était donnée à savoir mener une consultation sur le racisme systémique en lien avec les communautés LGBTQ+. Ce document en est la synthèse. Ainsi, pour la réalisation du présent rapport, nous avons recueilli 25 témoignages individuels. Toutes les personnes interviewées ont été victimes de racisme, certaines après avoir été témoin et être intervenues. Les 25 personnes entendues font partie de la communauté LGBTQ+ et sont racisées. Autant que faire se peut, nous avons essayé de recevoir des personnes représentant une grande diversité d’identités de genres et des sexualités. Sur la totalité des témoignages, nous avons donc pu nous entretenir avec des personnes s'identifiant comme lesbiennes, trans, bisexuelles, queers, gaies, studs ou encore pansexuelles.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; intersectionnalité; justice sociale; militance; montréal; premier cycle; périodes historiques; québec; racisme; régions géographiques; sciences humaines; sex2283; sociologie; systèmes d'oppressions; thématiques; violences

"A lot more to learn than where babies come from": Controversy, language and agenda setting in the framing of school-based sexuality education curricula in Australia - Shannon, Barrie; Smith, Stephen J. (Sex Education : Sexuality, Society and Learning, 2015)
Sexuality education in Australian schools continues to struggle in its ability and willingness to address many of the broader social issues associated with sexuality, such as the needs of gay, lesbian, bisexual, transgendered, intersex and queer (GLBTIQ) students. Studies involving teachers have demonstrated that a reticence on their part to teach GLBTIQ-inclusive sexuality education is driven by a lack of training in handling ‘sensitive’ issues, a fear of backlash and confusion over their obligations under relevant departmental policies. This reticence may, in part at least, stem from a commonly held inference that the inclusion of queer sexualities is inherently ‘controversial’. There appears to be a tendency for curricula and government directives to ‘juggle’ principles of social justice for marginalised sexualities with ‘risk management’ policies, which seek to screen course content for potential ‘controversy’. Much of this controversy has its roots in the language and rhetoric used to describe and discuss issues dealt with in sexuality education curricula. The paper demonstrates, through the process of ‘languaging’, how the language and rhetoric of controversy and sexuality can be exposed so that they may be better addressed through policy and government directives.
Keywords: EDI; LGBTQIA2+; adolescentes*; approches et analyses; asie; australie; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; inégalités; justice sociale; langage; programmes gouvernementaux; queer; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sociologie; systèmes d'oppressions; thématiques; éducation sexuelle

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Daniel Guérin et le discours militant sur l'homosexualité masculine en France (années 1950-années 1980) - Marchant, Alexandre (Revue d’histoire moderne & contemporaine, 2006)
Daniel Guérin (1904-1988), intellectuel marxiste et militant anarchiste, est un révélateur pour mesurer certaines transformations des représentations sociales de l’homosexualité en France, des années 1950 aux années 1980. Guérin incarne le passage d’un univers de discours (au sens de modèles de communication) à un autre,du légalisme arcadien à la perspective révolutionnaire du FHAR;de la discrétion à la politisation. Il a développé une pensée théorique originale de l’homosexualité, en rabattant celle-ci sur une bisexualité originelle. Sa réflexion sur les transformations sociales et historiques de l’identité homosexuelle inscrit la question des identités sexuelles dans une perspective nominaliste. Dans les années 1950 et 1960, les écrits de Guérin traitent de la répression de l’homosexualité en France. L’auteur donne également un éclairage particulier à la question de la révolution sexuelle des années 1970. Ses interventions littéraires ou publiques, dont la forme varie selon les contextes et les époques, ont encouragé la revendication politique d’une homosexualité stigmatisée juridiquement et réprimée policièrement.Néanmoins,de la fin des années 1970 à sa mort, il a durement critiqué l’essentialisation progressive de l’homosexualité au rang de marqueur identitaire.
Keywords: 1900-1999; EDI; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours militant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; identités LGBTQIA2+; justice sociale; marxisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

Le Rose et le noir : les homosexuels en France depuis 1968 - Martel, Frédéric (Éditions du Seuil, 1996)
"Ce livre est une chronique des homosexuels en France, hommes et femmes, depuis 1968. L’homosexualité est un fil rouge qui relie entre eux des phénomènes majeurs : libération sexuelle, féminisme, mutation des modes de vie, lutte contre le sida, pacs… Frédéric Martel évoque les figures emblématiques et les activistes, mais aussi les débats et les combats, tout ce qui a contribué à ce que les « gais » sortent de l’ombre. Plus visibles, mieux acceptés, les homosexuels sont aujourd’hui en quête de reconnaissance." – Site de l'éditeur
Section: 448 pages ; 24 cm
Keywords: 1900-1999; LGBTQIA2+; activisme; approches et analyses; cours; discipline; discours militant; droits des femmes*; europe; france; his4860; histoire du féminisme; histoire et politique; homosexualité; hétérosexisme; identités LGBTQIA2+; justice sociale; lesbianisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques

The rise of a gay and lesbian movement - Adam, Barry D. (Twayne, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis